Efficacy and safety of low‐dose oral isotretinoin monotherapy versus combined therapy with picosecond laser for the treatment of acne scars in Asian population. Issue 4 (1st March 2023) - Xue, Huan; Ye, Dan; Huang, Shiliu; He, Shujuan; Li, Youbao; Liu, Jing; Hu, Die; Zhu, Yu; Hu, Guanglei; Dong, Yan; Shen, Hua; Zeng, Wei‐Hui; et al.
Abstract: Purpose: Acne scars are common in patients with moderate to severe acne. Isotretinoin is the first‐line treatment for those patients, but whether oral isotretinoin can improve acne scar is not clear. Picosecond lasers (FxPico) has been reported to improve acne scars. In the present study, we evaluated the clinical efficacy of low‐dose isotretinoin with or without FxPico treatment for acne scars. Materials and Methods: A total of 48 patients with acne scars were enrolled and were randomly assigned to receive low dose oral isotretinoin or not. For all the patients in both treatment groups, one side of face were randomly assigned to be treated with picosecond laser. Assessments, including photos, échelle d'évaluation clinique des cicatrices d'acné (ECCA) and Global Acne Grading System (GAGS) score, the number of lesions, melanin and erythema indexes, transepidermal water loss were assessed at 0, 1, 2, and 3 month. Side effects, Dermatology Life Quality Index (DLQI) and satisfaction were recorded before and after the study. Results: A total of 44 patients completed the study (24 received oral low dose isotretinoin and 20 did not). Low dose oral isotretinoin treated group showed significant improvement on ECCA (from 112.5 [50–180] to 105 [50–160]), GAGS score (from 12.6 ± 3.3 to 10.1 ± 3.0), the count of papules (from 4.3 ± 3.7 to 1.0 ± 1.5) than the blank group, and higher improvement were noticed after isotretinoin combined with FxPico. All the side effects were temporary and tolerable, no adverse effects were observed. Higher DLQI and patients' satisfaction were achieved by oral isotretinoin alone and isotretinoin combined with FxPico. Conclusions: This is the first paper showing the improvement of scars by early low dose‐isotretinoin intervention with or without the combination of picosecond laser. Early intervention with oral low‐dose isotretinoin is effective for the treatment and prevention of acne scars, the combined therapy with FxPico can achieve better outcome.